(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Regardless of the advancements of humanistic notions in management theories and applications and the paradigm switch from an economistic perspective to a more humanistic one, current leadership literature still needs to be revised to propose alternatives for a modern economic worldview since it conforms to a mechanistic logic. The authors primarily emphasized highlighting the relevance of humanistic philosophy to organizational practices by reflecting on humanistic leadership insights from the specific case of Tata Group, which ensued by Tata Steel, and therefore, seek to contribute towards a leadership model based on humanism. The authors reviewed the literature on Humanistic Leadership tenets and practices to align it with the philosophy of the Tata Group, which is typically ingrained in Tata’s culture that shaped its underlying prosperity and sustainability and led it to expand holistic communal development. Humanistic Philosophy counterbalances the growing impact of the performance-driven managerial attitude and, therefore, assists managers in being more aware of the boundaries they should levy on specific performance measures. Thus, the authors contribute to humanistic leadership research and open up several avenues for future investigation into how modern leaders might exercise humanistic leadership.